Coal gasification slag-based self-foaming lightweight concrete and preparation method thereof
Through the preparation of coal gasification slag-based self-foaming lightweight concrete, mechanical grinding and microwave activation treatment, combined with waste incineration bottom ash and composite admixture, the problems of coal gasification slag disposal and low strength of foam concrete are solved, and high efficiency is achieved. Environmentally friendly lightweight concrete preparation, with good performance and convenient construction.
Patent Information
- Application Number
- CN202411030760.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2024-12-17
AI Technical Summary
There are problems such as the problem of disposing of existing coal gasification slag, low strength of foam concrete, many cracks, high cost, serious environmental pollution, and complex preparation process.
Use coal gasified slag-based self-foaming lightweight concrete to treat coal gasified fine slag through mechanical grinding and microwave activation, and combine waste incineration bottom ash, composite blends and excitants to form efficient gelling materials, using self-foaming and solidification The combined excitation of waste source alkali-salt can optimize the generation of hydration products and improve the strength and density of concrete.
It has achieved lightweight, high-strength, thermal insulation, sound insulation, noise reduction, waterproof and fireproof, convenient construction, reduced manufacturing costs and environmental pollution, simplified process flow, and promoted the resource utilization of solid waste.
Smart Images

Figure CN119143431A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lightweight foamed concrete and comprehensive utilization of solid waste, and in particular to a coal gasification slag-based self-foaming lightweight concrete and a preparation method thereof. Background Art
[0002] With the rapid development of economy and society, the demand for coal energy is increasing. As a powerful means to achieve clean utilization of coal, coal gasification is the leading technology of the modern coal chemical industry, which leads to the large-scale generation of coal gasification slag during the production process. Due to the complex carbon-ash combination in coal gasification slag, the serious pollution hazards of heavy metal ions such as chromium, mercury and lead, and the low reaction activity of residual carbon, it is difficult to separate and utilize it on a large scale. Only a part of it is used for residual carbon combustion, manufacturing construction materials, soil and water improvement and high-value utilization, etc. The rest is still mainly disposed of by storage, landfill and other methods.
[0003] Foam concrete usually uses the foaming system of a bubble machine to prepare a foaming agent aqueous solution into foam, and then add the foam to a slurry made of cement, aggregate, admixture, additives and water. After mixing, pouring, and curing, the resulting lightweight porous concrete has good lightweight, thermal insulation, heat insulation, fire resistance, sound insulation and frost resistance properties.
[0004] The cement production process consumes a large amount of non-renewable natural resources and energy and produces a large amount of toxic metals. At the same time, every ton of OPC produced will release 700kg of CO2 and some nitrogen and sulfur oxides into the air. These pollutants will cause abiotic depletion, global warming, and damage human health. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention discloses a coal gasification slag-based self-foaming lightweight concrete and a preparation method thereof, so as to solve the problems of large-scale and harmless disposal of existing coal gasification ash slag and the problems of low strength, many cracks, high cost, serious environmental pollution and complex preparation process of foamed concrete. The concrete has the characteristics of light weight and high strength, thermal insulation, sound insulation and noise reduction, waterproof and fireproof, and convenient construction.
[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a coal gasification slag-based self-foaming lightweight concrete, which comprises the following components by weight: 50-60 parts of coal gasification fine slag, 20-30 parts of waste incineration bottom ash, 10-30 parts of composite admixtures, 5-20 parts of composite activators, 20-40 parts of fine aggregates, 40-60 parts of water, 0.3-0.5 parts of sodium lactate, 0.3-0.5 parts of water reducers, 0.3-0.5 parts of cellulose ethers, and 0.3-0.5 parts of redispersible latex powders.
[0007] Furthermore, the coal gasification slag has a volatile matter content of 5-7%, a residual carbon content of 12-15%, and an ash content of 80-83% by weight; the chemical composition of the ash is as follows: SiO2 45-50%, Al2O3 16.5-18%, Fe2O3 10.5~11%, CaO17.3~20%; firstly, the coal gasification bottom slag is passed through a 20-mesh sieve to obtain coal gasification fine slag, the coal gasification fine slag is ground and activated by mechanical grinding, and a planetary ball mill is used to add a water reducer for 360° wet grinding to obtain coal gasification fine slag slurry, the rotation speed is controlled to be 340~380r / min, the ball-to-material ratio is 3:1~4:1, the water-to-material ratio is 2:1~3:1, and the grinding time is 40~80min; then the coal gasification fine slag slurry is dried to a moisture content of not more than 1%, and microwave activation treatment is performed to finally obtain coal gasification fine slag powder, the fineness of which meets the requirements of passing a 200-mesh sieve, the heating temperature is controlled to be 400~800℃, the insulation time is 2~4h, the microwave frequency is 2450MHz, and the microwave power is 400~1000W.
[0008] Furthermore, the waste incineration bottom ash contains different types of residues, including glass cullet, metals, ceramics and minerals, and the fineness meets the requirement of 90% passing through a 40-mesh sieve; the chemical composition of the waste incineration bottom ash, measured by weight percentage, is as follows: SiO2 45~50.5%, Al2O3 10.2~12.5%, Fe2O3 5.1~6.9%, CaO 16.3~17.5%, MgO 2.1~3%.
[0009] Furthermore, the composite admixture is composed of 40% rice husk ash and 60% metakaolin; the chemical composition of the rice husk ash, calculated by weight percentage, is as follows: SiO2 88.5~90%, Al2O3 0.3~0.5%, Fe2O3 0.5~0.8%, CaO 1.3~2%; the chemical composition of the metakaolin, calculated by weight percentage, is as follows: SiO2 55~58.5%, Al2O3 44~47.4%, Fe2O3 0.7~1%.
[0010] Furthermore, the composite activator is composed of 55% carbide slag and 45% desulfurized gypsum; the chemical composition of the carbide slag is as follows by weight percentage: SiO2 2.1~3.5%, Al2O3 0.5~1%, CaO 93~96%; the chemical composition of the desulfurized gypsum is as follows by weight percentage: SiO2 5.5~6.7%, CaO 39~42.3%, SO3 40.2~42.5%.
[0011] Furthermore, the fine aggregate is composed of 0.6-2.36 mm coal gasification coarse slag and coal gangue fine slag, and is soaked in 5% concentration polyvinyl alcohol solution for 1 day and then dried to a moisture content of no more than 1%; the coal gasification coarse slag is the residue of 20 mesh sieve of coal gasification slag.
[0012] A method for preparing coal gasification slag-based self-foaming lightweight concrete, specifically comprising the following steps: Step 1, weighing each component in parts by weight and drying to a moisture content of not more than 1%; Step 2, passing the coal gasification slag raw material through a 20-mesh sieve, adding a water reducer through a planetary ball mill, and performing 360° wet grinding for 40 to 80 minutes to obtain coal gasification fine slag slurry, and then drying the coal gasification fine slag slurry to a moisture content of no more than 1%, performing microwave activation treatment for 2 to 4 hours, and finally obtaining coal gasification fine slag; Step 3, soaking the coal gasification coarse slag and the coal gangue fine slag in a 5% concentration polyvinyl alcohol solution for 1 day and then drying them using the residual heat of microwave activation to obtain fine aggregate; Step 4, adding coal gasification fine slag, waste incineration bottom ash, composite admixture, composite activator and sodium lactate into a mixer and stirring them fully, adding water in equal parts by weight and stirring them fully to obtain a cementitious material mixed slurry; Step 5, adding fine aggregate, cellulose ether and redispersible latex powder to the cementitious material mixed slurry and stirring at high speed for 1-3 minutes, pouring into a mold and stopping to generate gas for 24 hours, then demolding and placing in a steam curing room with a temperature of 60-80° C. and a humidity of 95-98% for curing for 72 hours to obtain the coal gasification slag-based self-foaming lightweight concrete; Furthermore, all materials can be dried using the residual heat from the microwave activation in step 2.
[0013] Compared with the prior art, the present invention has the following characteristics: 1. The present invention is different from conventional foamed concrete in that it adopts a self-foaming method. The metal aluminum contained in the waste incineration bottom ash component can react with water in an alkaline environment, and the generated hydrogen immediately dissolves in the liquid phase. When a certain degree of supersaturation is reached, one or more bubble nuclei will be formed on the surface of the particles. On the other hand, the waste incineration bottom ash has rich aluminum silicate components, which can be used as a cementitious material precursor. The reaction generates a large amount of hydration products to form a skeleton support structure to provide strength.
[0014] 2. Based on the physical and chemical properties of raw materials and the synergistic coupling mechanism of multi-source solid waste, the present invention adopts a high-activity composite admixture of silicon-rich rice husk ash + aluminum-rich metakaolin, which can release active ions under alkaline conditions, further regulate the element ratio of calcium, silicon, aluminum and sulfur in the whole system, optimize the generation type and content of hydration products (CSH and AFt), and promote the formation of a dense microstructure, thereby ensuring the development of strength.
[0015] 3. The present invention is different from the conventional method of using strong alkali to stimulate solid waste. It uses the method of solid waste source alkali-salt combined stimulation. The Ca(OH)2 in carbide slag and CaSO4 in desulfurized gypsum can effectively promote the depolymerization of aluminosilicate in the cementitious material precursor, and further undergo polycondensation to generate a large amount of CSH and AFt. In addition, the composite activator can provide a large amount of calcium source for the system, which can increase the supersaturation of calcium ions in the solution, accelerate the hydration reaction, and provide higher early strength.
[0016] 4. Since the carbon ash binding mode in the coal gasification slag is complex and the residual carbon is high, resulting in low activity, the present invention uses mechanical activation + thermal activation pretreatment to treat the coal gasification slag. The wet grinding method with the addition of a water reducer can significantly reduce the surface binding energy of the powder, overcome the attraction between the powders, reduce the crushing resistance, prevent the ball from grinding, and improve the fluidity of the powder, thereby reducing the power consumption of the mill, improving the grinding efficiency, optimizing the particle size distribution, and further removing the residual carbon through microwave activation, while improving the reaction activity of the coal gasification slag.
[0017] 5. Since the gasification coarse slag and the coal gangue fine slag are porous and easy to absorb water, the present invention uses a 5% concentration of polyvinyl alcohol solution to pretreat the fine aggregate, which can increase the density of the aggregate, enhance the bonding of the interface transition zone, and prevent the rheological properties of the slurry from decreasing and the viscosity from decreasing.
[0018] 6. Compared with the prior art, the present invention provides a coal gasification slag-based self-foaming lightweight concrete and a preparation method thereof, which has the advantages of low manufacturing cost, low environmental pollution, simple process flow, and multiple maintenance methods. At the same time, the product has excellent performance in all aspects and can replace traditional foam concrete. It can effectively reduce the use of cement-based cementitious materials and promote the resource and large-scale utilization of solid waste materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1 The present invention is a flow chart of the preparation of the coal gasification slag-based self-foaming lightweight concrete. DETAILED DESCRIPTION
[0020] The present invention is further described in detail below in conjunction with specific examples. This example is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following examples.
[0021] A coal gasification slag-based self-foaming lightweight concrete, comprising the following components by weight: 50-60 parts of coal gasification fine slag, 20-30 parts of garbage incineration bottom ash, 10-30 parts of composite admixtures, 5-20 parts of composite activators, 20-40 parts of fine aggregates, 40-60 parts of water, 0.3-0.5 parts of sodium lactate, 0.3-0.5 parts of water reducing agent, 0.3-0.5 parts of cellulose ether, and 0.3-0.5 parts of redispersible latex powder.
[0022] Furthermore, the coal gasification slag has a volatile matter content of 5-7%, a residual carbon content of 12-15%, and an ash content of 80-83% by weight; the chemical composition of the ash is as follows: SiO2 45-50%, Al2O3 16.5-18%, Fe2O3 10.5~11%, CaO17.3~20%; firstly, the coal gasification bottom slag is passed through a 20-mesh sieve to obtain coal gasification fine slag, the coal gasification fine slag is ground and activated by mechanical grinding, and a planetary ball mill is used to add a water reducer for 360° wet grinding to obtain coal gasification fine slag slurry, the rotation speed is controlled to be 340~380r / min, the ball-to-material ratio is 3:1~4:1, the water-to-material ratio is 2:1~3:1, and the grinding time is 40~80min; then the coal gasification fine slag slurry is dried to a moisture content of not more than 1%, and microwave activation treatment is performed to finally obtain coal gasification fine slag powder, the fineness of which meets the requirements of passing a 200-mesh sieve, the heating temperature is controlled to be 400~800℃, the insulation time is 2~4h, the microwave frequency is 2450MHz, and the microwave power is 400~1000W.
[0023] Furthermore, the waste incineration bottom ash contains different types of residues, including glass cullet, metals, ceramics and minerals, and the fineness meets the requirement of 90% passing through a 40-mesh sieve; the chemical composition of the waste incineration bottom ash, measured by weight percentage, is as follows: SiO2 45~50.5%, Al2O3 10.2~12.5%, Fe2O3 5.1~6.9%, CaO 16.3~17.5%, MgO 2.1~3%.
[0024] Furthermore, the composite admixture is composed of 40% rice husk ash and 60% metakaolin; the chemical composition of the rice husk ash, calculated by weight percentage, is as follows: SiO2 88.5~90%, Al2O3 0.3~0.5%, Fe2O3 0.5~0.8%, CaO 1.3~2%; the chemical composition of the metakaolin, calculated by weight percentage, is as follows: SiO2 55~58.5%, Al2O3 44~47.4%, Fe2O3 0.7~1%.
[0025] Furthermore, the composite activator is composed of 55% carbide slag and 45% desulfurized gypsum; the chemical composition of the carbide slag is as follows by weight percentage: SiO2 2.1~3.5%, Al2O3 0.5~1%, CaO 93~96%; the chemical composition of the desulfurized gypsum is as follows by weight percentage: SiO2 5.5~6.7%, CaO 39~42.3%, SO3 40.2~42.5%.
[0026] Furthermore, the fine aggregate is composed of 0.6-2.36 mm coal gasification coarse slag and coal gangue fine slag, and is soaked in 5% concentration polyvinyl alcohol solution for 1 day and then dried to a moisture content of no more than 1%; the coal gasification coarse slag is the residue of 20 mesh sieve of coal gasification slag.
[0027] A method for preparing coal gasification slag-based self-foaming lightweight concrete, specifically comprising the following steps: Step 1, weighing each component in parts by weight and drying to a moisture content of not more than 1%; Step 2, passing the coal gasification slag raw material through a 20-mesh sieve, adding a water reducer through a planetary ball mill, and performing 360° wet grinding for 40 to 80 minutes to obtain coal gasification fine slag slurry, and then drying the coal gasification fine slag slurry to a moisture content of no more than 1%, performing microwave activation treatment for 2 to 4 hours, and finally obtaining coal gasification fine slag; Step 3, soaking the coal gasification coarse slag and the coal gangue fine slag in a 5% concentration polyvinyl alcohol solution for 1 day and then drying them using the residual heat of microwave activation to obtain fine aggregate; Step 4, adding coal gasification fine slag, waste incineration bottom ash, composite admixture, composite activator and sodium lactate into a mixer and stirring them fully, adding water in equal parts by weight and stirring them fully to obtain a cementitious material mixed slurry; Step 5, adding fine aggregate, cellulose ether and redispersible latex powder to the cementitious material mixed slurry and stirring at high speed for 1-3 minutes, pouring into a mold and standing to gasify for 24 hours, then demolding and placing in a steam curing room with a temperature of 60-80° C. and a humidity of 95-98% for curing for 72 hours to obtain the coal gasification slag-based self-foaming lightweight concrete. Example
[0028] A coal gasification slag-based self-foaming lightweight concrete, comprising the following components by weight: 50 parts of coal gasification fine slag, 20 parts of garbage incineration bottom ash, 30 parts of composite admixtures, 20 parts of composite activators, 30 parts of fine aggregates, 40 parts of water, 0.5 parts of sodium lactate, 0.3 parts of water reducing agent, 0.5 parts of cellulose ether, and 0.3 parts of redispersible latex powder.
[0029] Furthermore, the coal gasification slag has a volatile matter content of 5-7%, a residual carbon content of 12-15%, and an ash content of 80-83% by weight; the chemical composition of the ash is as follows: SiO2 45-50%, Al2O3 16.5-18%, Fe2O3 10.5~11%, CaO17.3~20%; firstly, the coal gasification bottom slag is passed through a 20-mesh sieve to obtain coal gasification fine slag, the coal gasification fine slag is ground and activated by mechanical grinding, and a planetary ball mill is used to add a water reducer for 360° wet grinding to obtain coal gasification fine slag slurry, the rotation speed is controlled to be 360r / min, the ball-to-material ratio is 4:1, the water-to-material ratio is 2:1, and the grinding time is 40min; then the coal gasification fine slag slurry is dried to a moisture content of not more than 1%, and microwave activation treatment is performed to finally obtain coal gasification fine slag powder with a fineness that meets the 200-mesh sieve, the heating temperature is controlled to be 500℃, the insulation time is 4h, the microwave frequency is 2450MHz, and the microwave power is 800W.
[0030] Furthermore, the waste incineration bottom ash contains different types of residues, including glass cullet, metals, ceramics and minerals, and the fineness meets the requirement of 90% passing through a 40-mesh sieve; the chemical composition of the waste incineration bottom ash, measured by weight percentage, is as follows: SiO2 45~50.5%, Al2O3 10.2~12.5%, Fe2O3 5.1~6.9%, CaO 16.3~17.5%, MgO 2.1~3%.
[0031] Furthermore, the composite admixture is composed of 40% rice husk ash and 60% metakaolin; the chemical composition of the rice husk ash, calculated by weight percentage, is as follows: SiO2 88.5~90%, Al2O3 0.3~0.5%, Fe2O3 0.5~0.8%, CaO 1.3~2%; the chemical composition of the metakaolin, calculated by weight percentage, is as follows: SiO2 55~58.5%, Al2O3 44~47.4%, Fe2O3 0.7~1%.
[0032] Furthermore, the composite activator is composed of 55% carbide slag and 45% desulfurized gypsum; the chemical composition of the carbide slag is as follows by weight percentage: SiO2 2.1~3.5%, Al2O3 0.5~1%, CaO 93~96%; the chemical composition of the desulfurized gypsum is as follows by weight percentage: SiO2 5.5~6.7%, CaO 39~42.3%, SO3 40.2~42.5%.
[0033] Furthermore, the fine aggregate is composed of 0.6-2.36 mm coal gasification coarse slag and coal gangue fine slag, and is soaked in 5% concentration polyvinyl alcohol solution for 1 day and then dried to a moisture content of no more than 1%; the coal gasification coarse slag is the residue of 20 mesh sieve of coal gasification slag.
[0034] A method for preparing coal gasification slag-based self-foaming lightweight concrete, specifically comprising the following steps: Step 1, weighing each component in parts by weight and drying to a moisture content of not more than 1%; Step 2, passing the coal gasification slag raw material through a 20-mesh sieve, adding a water reducer through a planetary ball mill and performing 360° wet grinding for 40 minutes to obtain coal gasification fine slag slurry, and then drying the coal gasification fine slag slurry to a moisture content of no more than 1%, performing microwave activation treatment for 4 hours, and finally obtaining coal gasification fine slag; Step 3, soaking the coal gasification coarse slag and the coal gangue fine slag in a 5% concentration polyvinyl alcohol solution for 1 day and then drying them using the residual heat of microwave activation to obtain fine aggregate; Step 4, adding coal gasification fine slag, waste incineration bottom ash, composite admixture, composite activator and sodium lactate into a mixer and stirring them fully, adding water in equal parts by weight and stirring them fully to obtain a cementitious material mixed slurry; Step 5, adding fine aggregate, cellulose ether and redispersible latex powder to the cementitious material mixed slurry and stirring at high speed for 2 minutes, pouring into a mold and standing to gasify for 24 hours, then demolding and placing in a steam curing room with a temperature of 80° C. and a humidity of 95% for curing for 72 hours to obtain the coal gasification slag-based self-foaming lightweight concrete. Example
[0035] A coal gasification slag-based self-foaming lightweight concrete, comprising the following components by weight: 50 parts of coal gasification fine slag, 30 parts of garbage incineration bottom ash, 20 parts of composite admixtures, 15 parts of composite activators, 40 parts of fine aggregates, 50 parts of water, 0.4 parts of sodium lactate, 0.4 parts of water reducing agent, 0.5 parts of cellulose ether, and 0.5 parts of redispersible latex powder.
[0036] Furthermore, the coal gasification slag has a volatile matter content of 5-7%, a residual carbon content of 12-15%, and an ash content of 80-83% by weight; the chemical composition of the ash is as follows: SiO2 45-50%, Al2O3 16.5-18%, Fe2O3 10.5~11%, CaO17.3~20%; firstly, the coal gasification bottom slag is passed through a 20-mesh sieve to obtain coal gasification fine slag, the coal gasification fine slag is ground and activated by mechanical grinding, and a planetary ball mill is used to add a water reducer for 360° wet grinding to obtain coal gasification fine slag slurry, the speed is controlled to be 360r / min, the ball-to-material ratio is 4:1, the water-to-material ratio is 2:1, and the grinding time is 60min; then the coal gasification fine slag slurry is dried to a moisture content of not more than 1%, and microwave activation treatment is performed to finally obtain coal gasification fine slag powder with a fineness that meets the 200-mesh sieve, the heating temperature is controlled to be 500℃, the insulation time is 3h, the microwave frequency is 2450MHz, and the microwave power is 800W.
[0037] Furthermore, the waste incineration bottom ash contains different types of residues, including glass cullet, metals, ceramics and minerals, and the fineness meets the requirement of 90% passing through a 40-mesh sieve; the chemical composition of the waste incineration bottom ash, measured by weight percentage, is as follows: SiO2 45~50.5%, Al2O3 10.2~12.5%, Fe2O3 5.1~6.9%, CaO 16.3~17.5%, MgO 2.1~3%.
[0038] Furthermore, the composite admixture is composed of 40% rice husk ash and 60% metakaolin; the chemical composition of the rice husk ash, calculated by weight percentage, is as follows: SiO2 88.5~90%, Al2O3 0.3~0.5%, Fe2O3 0.5~0.8%, CaO 1.3~2%; the chemical composition of the metakaolin, calculated by weight percentage, is as follows: SiO2 55~58.5%, Al2O3 44~47.4%, Fe2O3 0.7~1%.
[0039] Furthermore, the composite activator is composed of 55% carbide slag and 45% desulfurized gypsum; the chemical composition of the carbide slag is as follows by weight percentage: SiO2 2.1~3.5%, Al2O3 0.5~1%, CaO 93~96%; the chemical composition of the desulfurized gypsum is as follows by weight percentage: SiO2 5.5~6.7%, CaO 39~42.3%, SO3 40.2~42.5%.
[0040] Furthermore, the fine aggregate is composed of 0.6-2.36 mm coal gasification coarse slag and coal gangue fine slag, and is soaked in 5% concentration polyvinyl alcohol solution for 1 day and then dried to a moisture content of no more than 1%; the coal gasification coarse slag is the residue of 20 mesh sieve of coal gasification slag.
[0041] A method for preparing coal gasification slag-based self-foaming lightweight concrete, specifically comprising the following steps: Step 1, weighing each component in parts by weight and drying to a moisture content of not more than 1%; Step 2, passing the coal gasification slag raw material through a 20-mesh sieve, adding a water reducer through a planetary ball mill, and performing 360° wet grinding for 60 minutes to obtain coal gasification fine slag slurry, and then drying the coal gasification fine slag slurry to a moisture content of no more than 1%, performing microwave activation treatment for 3 hours, and finally obtaining coal gasification fine slag; Step 3, soaking the coal gasification coarse slag and the coal gangue fine slag in a 5% concentration polyvinyl alcohol solution for 1 day and then drying them using the residual heat of microwave activation to obtain fine aggregate; Step 4, adding coal gasification fine slag, waste incineration bottom ash, composite admixture, composite activator and sodium lactate into a mixer and stirring them fully, adding water in equal parts by weight and stirring them fully to obtain a cementitious material mixed slurry; Step 5, adding fine aggregate, cellulose ether and redispersible latex powder to the cementitious material mixed slurry and stirring at high speed for 2 minutes, pouring into a mold and standing to gasify for 24 hours, then demolding and placing in a steam curing room with a temperature of 80° C. and a humidity of 95% for curing for 72 hours to obtain the coal gasification slag-based self-foaming lightweight concrete. Example
[0042] A coal gasification slag-based self-foaming lightweight concrete, comprising the following components by weight: 60 parts of coal gasification fine slag, 30 parts of garbage incineration bottom ash, 10 parts of composite admixtures, 10 parts of composite activators, 20 parts of fine aggregates, 60 parts of water, 0.3 parts of sodium lactate, 0.5 parts of water reducing agent, 0.7 parts of cellulose ether, and 0.5 parts of redispersible latex powder.
[0043] Furthermore, the coal gasification slag has a volatile matter content of 5-7%, a residual carbon content of 12-15%, and an ash content of 80-83% by weight; the chemical composition of the ash is as follows: SiO2 45-50%, Al2O3 16.5-18%, Fe2O3 10.5~11%, CaO17.3~20%; firstly, the coal gasification bottom slag is passed through a 20-mesh sieve to obtain coal gasification fine slag, the coal gasification fine slag is ground and activated by mechanical grinding, and a planetary ball mill is used to add a water reducer for 360° wet grinding to obtain coal gasification fine slag slurry, the speed is controlled to be 360r / min, the ball-to-material ratio is 4:1, the water-to-material ratio is 2:1, and the grinding time is 80min; then the coal gasification fine slag slurry is dried to a moisture content of not more than 1%, and microwave activation treatment is performed to finally obtain coal gasification fine slag powder with a fineness that meets the 200-mesh sieve, the heating temperature is controlled to be 500℃, the insulation time is 2h, the microwave frequency is 2450MHz, and the microwave power is 800W.
[0044] Furthermore, the waste incineration bottom ash contains different types of residues, including glass cullet, metals, ceramics and minerals, and the fineness meets the requirement of 90% passing through a 40-mesh sieve; the chemical composition of the waste incineration bottom ash, measured by weight percentage, is as follows: SiO2 45~50.5%, Al2O3 10.2~12.5%, Fe2O3 5.1~6.9%, CaO 16.3~17.5%, MgO 2.1~3%.
[0045] Furthermore, the composite admixture is composed of 40% rice husk ash and 60% metakaolin; the chemical composition of the rice husk ash, calculated by weight percentage, is as follows: SiO2 88.5~90%, Al2O3 0.3~0.5%, Fe2O3 0.5~0.8%, CaO 1.3~2%; the chemical composition of the metakaolin, calculated by weight percentage, is as follows: SiO2 55~58.5%, Al2O3 44~47.4%, Fe2O3 0.7~1%.
[0046] Furthermore, the composite activator is composed of 55% carbide slag and 45% desulfurized gypsum; the chemical composition of the carbide slag is as follows by weight percentage: SiO2 2.1~3.5%, Al2O3 0.5~1%, CaO 93~96%; the chemical composition of the desulfurized gypsum is as follows by weight percentage: SiO2 5.5~6.7%, CaO 39~42.3%, SO3 40.2~42.5%.
[0047] Furthermore, the fine aggregate is composed of 0.6-2.36 mm coal gasification coarse slag and coal gangue fine slag, and is soaked in 5% concentration polyvinyl alcohol solution for 1 day and then dried to a moisture content of no more than 1%; the coal gasification coarse slag is the residue of 20 mesh sieve of coal gasification slag.
[0048] A method for preparing coal gasification slag-based self-foaming lightweight concrete, specifically comprising the following steps: Step 1, weighing each component in parts by weight and drying to a moisture content of not more than 1%; Step 2, passing the coal gasification slag raw material through a 20-mesh sieve, adding a water reducer through a planetary ball mill, and performing 360° wet grinding for 80 minutes to obtain coal gasification fine slag slurry, and then drying the coal gasification fine slag slurry to a moisture content of no more than 1%, performing microwave activation treatment for 2 hours, and finally obtaining coal gasification fine slag; Step 3, soaking the coal gasification coarse slag and the coal gangue fine slag in a 5% concentration polyvinyl alcohol solution for 1 day and then drying them using the residual heat of microwave activation to obtain fine aggregate; Step 4, adding coal gasification fine slag, waste incineration bottom ash, composite admixture, composite activator and sodium lactate into a mixer and stirring them fully, adding water in equal parts by weight and stirring them fully to obtain a cementitious material mixed slurry; Step 5, adding fine aggregate, cellulose ether and redispersible latex powder to the cementitious material mixed slurry and stirring at high speed for 2 minutes, pouring into a mold and standing to gasify for 24 hours, then demolding and placing in a steam curing room with a temperature of 80° C. and a humidity of 95% for curing for 72 hours to obtain the coal gasification slag-based self-foaming lightweight concrete. Example
[0049] A coal gasification slag-based self-foaming lightweight concrete, comprising the following components by weight: 55 parts of coal gasification fine slag, 20 parts of garbage incineration bottom ash, 25 parts of composite admixtures, 15 parts of composite activators, 30 parts of fine aggregates, 50 parts of water, 0.4 parts of sodium lactate, 0.4 parts of water reducing agent, 0.6 parts of cellulose ether, and 0.4 parts of redispersible latex powder.
[0050] Furthermore, the coal gasification slag has a volatile matter content of 5-7%, a residual carbon content of 12-15%, and an ash content of 80-83% by weight; the chemical composition of the ash is as follows: SiO2 45-50%, Al2O3 16.5-18%, Fe2O3 10.5~11%, CaO17.3~20%; firstly, the coal gasification bottom slag is passed through a 20-mesh sieve to obtain coal gasification fine slag, the coal gasification fine slag is ground and activated by mechanical grinding, and a planetary ball mill is used to add a water reducer for 360° wet grinding to obtain coal gasification fine slag slurry, the speed is controlled to be 360r / min, the ball-to-material ratio is 4:1, the water-to-material ratio is 2:1, and the grinding time is 80min; then the coal gasification fine slag slurry is dried to a moisture content of not more than 1%, and microwave activation treatment is performed to finally obtain coal gasification fine slag powder with a fineness that meets the 200-mesh sieve, the heating temperature is controlled to be 500℃, the insulation time is 4h, the microwave frequency is 2450MHz, and the microwave power is 800W.
[0051] Furthermore, the waste incineration bottom ash contains different types of residues, including glass cullet, metals, ceramics and minerals, and the fineness meets the requirement of 90% passing through a 40-mesh sieve; the chemical composition of the waste incineration bottom ash, measured by weight percentage, is as follows: SiO2 45~50.5%, Al2O3 10.2~12.5%, Fe2O3 5.1~6.9%, CaO 16.3~17.5%, MgO 2.1~3%.
[0052] Furthermore, the composite admixture is composed of 40% rice husk ash and 60% metakaolin; the chemical composition of the rice husk ash, calculated by weight percentage, is as follows: SiO2 88.5~90%, Al2O3 0.3~0.5%, Fe2O3 0.5~0.8%, CaO 1.3~2%; the chemical composition of the metakaolin, calculated by weight percentage, is as follows: SiO2 55~58.5%, Al2O3 44~47.4%, Fe2O3 0.7~1%.
[0053] Furthermore, the composite activator is composed of 55% carbide slag and 45% desulfurized gypsum; the chemical composition of the carbide slag is as follows by weight percentage: SiO2 2.1~3.5%, Al2O3 0.5~1%, CaO 93~96%; the chemical composition of the desulfurized gypsum is as follows by weight percentage: SiO2 5.5~6.7%, CaO 39~42.3%, SO3 40.2~42.5%.
[0054] Furthermore, the fine aggregate is composed of 0.6-2.36 mm coal gasification coarse slag and coal gangue fine slag, and is soaked in 5% concentration polyvinyl alcohol solution for 1 day and then dried to a moisture content of no more than 1%; the coal gasification coarse slag is the residue of 20 mesh sieve of coal gasification slag.
[0055] A method for preparing coal gasification slag-based self-foaming lightweight concrete, specifically comprising the following steps: Step 1, weighing each component in parts by weight and drying to a moisture content of not more than 1%; Step 2, passing the coal gasification slag raw material through a 20-mesh sieve, adding a water reducer through a planetary ball mill, and performing 360° wet grinding for 80 minutes to obtain coal gasification fine slag slurry, and then drying the coal gasification fine slag slurry to a moisture content of no more than 1%, performing microwave activation treatment for 4 hours, and finally obtaining coal gasification fine slag; Step 3, soaking the coal gasification coarse slag and the coal gangue fine slag in a 5% concentration polyvinyl alcohol solution for 1 day and then drying them using the residual heat of microwave activation to obtain fine aggregate; Step 4, adding coal gasification fine slag, waste incineration bottom ash, composite admixture, composite activator and sodium lactate into a mixer and stirring them fully, adding water in equal parts by weight and stirring them fully to obtain a cementitious material mixed slurry; Step 5, adding fine aggregate, cellulose ether and redispersible latex powder to the cementitious material mixed slurry and stirring at high speed for 2 minutes, pouring into a mold and standing to gasify for 24 hours, then demolding and placing in a steam curing room with a temperature of 80° C. and a humidity of 95% for curing for 72 hours to obtain the coal gasification slag-based self-foaming lightweight concrete.
[0056] Table 1 shows the performance results of lightweight concrete of Examples 1-4.
[0057] Performance Indicators Example 1 Example 2 Example 3 Example 4 Absolute dry density / kg / m3 739 703 668 686 Compressive strength / MPa 5.86 5.53 5.17 5.35 Thermal conductivity / W·(m·k)-1 0.178 0.165 0.168 0.162 Water absorption / % 8.53 8.87 9.57 9.26 Freeze-thaw strength loss rate / % ≤20 ≤20 ≤20 ≤20 Freeze-thaw mass loss rate / % ≤5.0 ≤5.0 ≤5.0 ≤5.0 It can be seen from the above test data results that the lightweight concrete prepared by the method provided by the present invention meets the standards "Foamed Concrete" (JG / T 266-2011) and "Autoclaved Aerated Concrete Block" (GB / T 11968-2020).
[0058] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. Coal gasification slag-based self-foaming lightweight concrete, characterized by: The coal gasification slag-based self-foaming lightweight concrete comprises the following components by weight: 50-60 parts of coal gasification fine slag, 20-30 parts of garbage incineration bottom ash, 10-30 parts of composite admixtures, 5-20 parts of composite activators, 20-40 parts of fine aggregates, 40-60 parts of water, 0.3-0.5 parts of sodium lactate, 0.3-0.5 parts of water reducing agent, 0.3-0.5 parts of cellulose ether, and 0.3-0.5 parts of redispersible latex powder.
2. The coal gasification slag-based self-foaming lightweight concrete according to claim 1, characterized in that: The coal gasification fine slag has a volatile matter content of 5-7%, a residual carbon content of 12-15%, and an ash content of 80-83% by weight; the chemical composition of the ash is as follows: SiO2 45-50%, Al2O3 16.5-18%, Fe2O3 10.5-11%, and CaO 17.3-20%.
3. The coal gasification slag-based self-foaming lightweight concrete according to claim 1, characterized in that: The waste incineration bottom ash includes glass cullet, metal, ceramic and mineral. The chemical composition of the waste incineration bottom ash is as follows by weight percentage: SiO2 45-50.5%, Al2O3 10.2-12.5%, Fe2O3 5.1-6.9%, CaO 16.3-17.5%, and MgO 2.1-3%.
4. The coal gasification slag-based self-foaming lightweight concrete according to claim 1, characterized in that: The composite admixture includes 40% rice husk ash and 60% kaolin; the chemical composition of the rice husk ash, calculated by weight percentage, is as follows: SiO2 88.5-90%, Al2O3 0.3-0.5%, Fe2O3 0.5-0.8%, CaO 1.3-2%; the chemical composition of the kaolin, calculated by weight percentage, is as follows: SiO2 55-58.5%, Al2O3 44-47.4%, Fe2O3 0.7-1%.
5. The coal gasification slag-based self-foaming lightweight concrete according to claim 1, characterized in that: The composite activator includes 55% carbide slag and 45% desulfurized gypsum; the carbide slag has the following chemical composition by weight: SiO2 2.1-3.5%, Al2O3 0.5-1%, CaO 93-96%; the desulfurized gypsum has the following chemical composition by weight: SiO2 5.5-6.7%, CaO 39-42.3%, SO3 40.2-42.5%.
6. The coal gasification slag-based self-foaming lightweight concrete according to claim 1, characterized in that: The fine aggregate includes 0.6-2.36 mm coal gasification coarse slag and coal gangue fine slag.
7. The method for preparing the coal gasification slag-based self-foaming lightweight concrete according to claim 1, characterized in that: The specific steps include: 1) Weigh each component according to the weight percentage and dry it to a moisture content of no more than 1%; 2) The coal gasification bottom slag raw material is passed through a 20-mesh sieve, and a water reducer is added to perform 360° wet grinding for 40 to 80 minutes in a planetary ball mill to obtain coal gasification fine slag slurry, and then the coal gasification fine slag slurry is dried to a moisture content of no more than 1%, and microwave activation treatment is performed for 2 to 4 hours to finally obtain coal gasification fine slag; 3) soaking the gasification coarse slag and the gangue fine slag in a 5% polyvinyl alcohol solution for 1 day and drying them using the residual heat of microwave activation to obtain fine aggregate; 4) adding coal gasification fine slag, garbage incineration bottom ash, composite admixture, composite activator and sodium lactate into a mixer and stirring them fully, adding water in equal parts by weight and stirring them fully to obtain a cementitious material mixed slurry; 5) Add fine aggregate, cellulose ether and redispersible latex powder to the cementitious material mixed slurry and stir at high speed for 1-3 minutes, pour into a mold and let it stand for 24 hours to generate gas, then demold and put into a steam curing room with a temperature of 60-80° C. and a humidity of 95-98% for 72 hours to obtain the coal gasification slag-based self-foaming lightweight concrete.
8. The method for preparing the coal gasification slag-based self-foaming lightweight concrete according to claim 7, wherein the method for preparing the coal gasification fine slag comprises firstly passing the coal gasification bottom slag through a 20-mesh sieve to obtain coal gasification fine slag, grinding and activating the coal gasification fine slag by mechanical grinding, and using a planetary ball mill to add a water reducer for 360° wet grinding to obtain coal gasification fine slag slurry, wherein the rotation speed is controlled to be 340-380 r / min, the ball-to-material ratio is 3:1-4:1, the water-to-material ratio is 2:1-3:1, and the grinding time is 40-80 min; then the coal gasification fine slag slurry is dried to a moisture content of not more than 1%, and microwave activation treatment is performed to finally obtain coal gasification fine slag powder, the fineness of which meets the requirements of passing a 200-mesh sieve, the heating temperature is controlled to be 400-800°C, the insulation time is 2-4 h, the microwave frequency is 2450 MHz, and the microwave power is 400-1000 W.
9. The method for preparing coal gasification slag-based self-foaming lightweight concrete according to claim 7, characterized in that: The fineness of the waste incineration bottom ash is such that 90% of it passes through a 40-mesh sieve.
10. The method for preparing coal gasification slag-based self-foaming lightweight concrete according to claim 7, characterized in that: All materials can be dried using the residual heat from the microwave activation in step 2.
Citation Information
Cited By
All-solid waste self-foaming gel and concrete based on papermaking black liquid and preparation method of all-solid waste self-foaming gel and concrete
CN120483556A
All-solid-waste self-foaming gel and concrete based on papermaking black liquor and method for preparing same
CN120483556B
